Analisis Framing Portal Berita Kompas.Com dan Mediaindonesia.Com atas Pemberitaan Program Makan Siang Gratis oleh Paslon 02 (Prabowo-Gibran) Pada Periode 28 November 2023 - 10 Februari 2024 - Nainggolan, Imelda Dwi Putri; Claretta, Dyva (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
2024 is a crucial year for Indonesia as it marks the presidential and vice-presidential transition. The General Elections Commission (KPU) has nominated three candidate pairs, one of which is Prabowo Subianto-Gibran Rakabuming Raka (candidate pair 02), who proposed a free lunch program. This program has sparked considerable debate in various media, prompting this study to analyze the framing of news coverage about the free lunch program by candidate pair 02 (Prabowo-Gibran) on the online news portals Kompas.com and Mediaindonesia.com during the period of November 28, 2024, to February 10, 2024. The research employs a descriptive qualitative method to describe or explain the underlying meanings of reality. Data analysis is conducted using Zhongdang Pan and Gerald M. Kosicki's framing analysis model, which includes syntactic, script, thematic, and rhetorical structures. The findings indicate that Kompas.com’s coverage is supportive of the free lunch program. On the other hand, the coverage on Mediaindonesia.com is firmly against the free lunch program